IMPROVING EFFECT OF PLATYCODIN D ON ETHANOL-INDUCED FATTY LIVER VIA KEAP1-NRF2-ARE SIGNAL PATH - Wu, Jingtao; Zhou, Lei; Yang, Guiwen; Tao, Fan; Wang, Maoshan; Hu, Jianguo (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Platycodin D (PD) is one of the important active ingredients in the root of the Platycodon grandiflorum(Jacq.) A. DC (PG), a traditional medicine with many pharmacological activities, especially hepatoprotective activity.There are some researches on the mechanism of liver protection, but it is not very clear. It is necessary to investigate itdeeply.Materials and Methods: In order to evaluate the effect of PD on ethanol-induced fatty liver (EFL) and investigate thepossible mechanism, the EFL models of rats and BRL-3A cells were set up and treated with PD of 20, 30 mg/kg bodyweight/day for four weeks, respectively. The hepatic histochemistry, liver function enzymes, oxidative stress levels,antioxidant enzymes and signal path enzymes were assayed.Results: PD significantly (P<0.01) activates signal path enzymes of Keap1, Nrf2 and small Maf either in vitro or invivo, increases hepatic antioxidant enzyme expression of HO-1, SOD and GSH-Px, improves the oxidative stressindicated by CYP2E1, ROS, T-AOC capacity and MDA contents, reduces levels of serum ALT and AST, and thenimproves the liver injury degree by histological evaluation.Conclusion: PD is an effective inhibitor of EFL to ameliorate liver impairment ethanol-induced via Keap1-Nrf2-AREsignal path.